2012
DOI: 10.2174/1874241601003010019
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine: An Emerging Cardiovascular Risk Factor that Never Really Made it~!2009-10-29~!2009-12-27~!2010-04-08~!

Abstract: Serum total homocysteine (tHcy) has been implicated in promoting venous thromboembolic events and atherosclerosis, manifested as coronary heart disease, stroke or peripheral arterial disease. Dietary supplementation with B vitamins that lower tHcy concentrations was expected to reduce cardiovascular disease (CVD) risk. However, recent metaanalyses of prospective observational studies and randomized controlled trials failed to show a role of tHcy in the pathogenesis of vascular disease or a benefit of B vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…There is strong evidence from laboratory and clinical studies that eHcy is an independent risk factor for cardiovascular disease, although some recent studies appear to refute this claim. 12 The findings of these laboratory studies and clinical observations suggest that eHcy exerts toxic effects on endothelial cells, the vascular wall structure, and the blood coagulation system. 4 The actions of eHcy on vascular endothelial cells lead to the proliferation of smooth-muscle cells, promote the oxidation of low-density lipoprotein, and increase collagen synthesis and procoagulant activity, with all of these actions accounting for the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 94%
“…There is strong evidence from laboratory and clinical studies that eHcy is an independent risk factor for cardiovascular disease, although some recent studies appear to refute this claim. 12 The findings of these laboratory studies and clinical observations suggest that eHcy exerts toxic effects on endothelial cells, the vascular wall structure, and the blood coagulation system. 4 The actions of eHcy on vascular endothelial cells lead to the proliferation of smooth-muscle cells, promote the oxidation of low-density lipoprotein, and increase collagen synthesis and procoagulant activity, with all of these actions accounting for the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast to the findings of non-American studies, the MTHFR genotypes were found to have no effect on DVT in North America due probably to the higher intake of folate and riboflavin in this population. 29,30 The b-chain synthesis has been shown to be a rate-limiting step in fibrinogen production, and any mutation related with the b-fibrinogen gene or its transcription may have an impact on plasma fibrinogen levels. 31 However, the association between the b-fibrinogen gene polymorphism and VTE remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the findings of non-American studies, the MTHFR genotypes were found to have no effect on DVT in North America due probably to the higher intake of folate and riboflavin in this population. 29,30…”
Section: Discussionmentioning
confidence: 99%